2012
DOI: 10.1080/01635581.2012.630158
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Mechanisms of Green Tea Catechins in the Chemoprevention of Prostate Cancer

Abstract: Prostate cancer is the most commonly diagnosed cancer and second most common cause of cancer deaths in American men. Its long latency, slow progression, and high incidence rate make prostate cancer ideal for targeted chemopreventative therapies. Therefore, chemoprevention studies and clinical trials are essential for reducing the burden of prostate cancer on society. Epidemiological studies suggest that tea consumption has protective effects against a variety of human cancers, including that of the prostate. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 173 publications
(406 reference statements)
1
52
0
2
Order By: Relevance
“…Similar effects have been described for two synthetic enantiomeric analogs of natural GTCs in PCa cells [133]. The observed accumulation of short-lived proteins, normally addressed to proteosomal degradation such as p21, p27, Bax and ikΒα, in PCa cells after EGCG or GTCs treatment indirectly confirms, that GTCs exert inhibitory effect on the proteasome activity [98,134].…”
Section: Proteasome Inhibitionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar effects have been described for two synthetic enantiomeric analogs of natural GTCs in PCa cells [133]. The observed accumulation of short-lived proteins, normally addressed to proteosomal degradation such as p21, p27, Bax and ikΒα, in PCa cells after EGCG or GTCs treatment indirectly confirms, that GTCs exert inhibitory effect on the proteasome activity [98,134].…”
Section: Proteasome Inhibitionsupporting
confidence: 62%
“…Effects of GTCs on GSTP1reexpression are discussed in the next paragraph. NF-kB is constitutively activated in PCa cells, prostate premalignant lesions (intraepithelial tumors, PIN) and PCa tissues [98]. EGCG has been demonstrated to inhibit NF-kB [99,102] and in TRAMP mice [16].…”
Section: Effects Of Gtcs On Regulation Of Gene Expressionmentioning
confidence: 99%
“…Most dealt with cancer in general or mechanistic aspects of carcinogenesis, only a few reviews focused on the prevention of specific cancer types like lung cancer [39][40][41], breast cancer [42,43], colon cancer [44], prostate cancer [14,[45][46][47] and gastric cancer [48]. Epidemiological evidence for the protective effects of GTE for cancer of all types has been reviewed in 2009 by Boehm et al [37], using the Cochrane collaboration criteria for randomized prospective studies.…”
Section: Green Tea and Cancermentioning
confidence: 99%
“…Epigallocatechin-3-gallate, a major ingredient of Green tea catechins , has been reported to exert a variety of biological effects, including antioxidant, antibacterial, anti-inflammatory and anticarcinogenic activities. Additionally, it has been reported that this ingredient inhibits lipopolysaccharide (LPS)-induced inflammatory cytokine production [81][82][83].…”
Section: Maintenance Of Oral Hygienementioning
confidence: 99%